Microbial characterization based on multifractal analysis of metagenomes - Xie, Xian-hua; Huang, Yu-jie; Han, Guo-sheng; Yu, Zu-guo; Ma, Yuan-lin (Frontiers in Cellular and Infection Microbiology, 2023)
The species diversity of microbiome is a cutting-edge concept in metagenomic research. In this study, we propose a multifractal analysis for metagenomic research. By visualizing the Chaotic Game Representation (CGR) of simulated metagenomes and real metagenomes, we find that metagenomes are visualized with self-similarity. We calculate the multifractal dimensions of simulated and real metagenomes respectively. For simulated metagenomes, we also calculate three diversity indices, such as species richness indices, Shannon diversity indices and Simpson diversity indices. By analyzing the Pearson correlation coefficients between the multifractal dimension and the traditional species diversity index, we obtain that the correlation coefficient between the multifractal dimension and the species richness index and Shannon diversity index reached the maximum value when q = 0,1, and the correlation coefficient between the multifractal dimension and the Simpson diversity index reached the maximum value when q = 5. Therefore, the traditional diversity indicators can be unified under the framework of multifractal analysis. These results coincided with the similar results in macrobial ecology. Finally, we apply our method to real metagenomes of the gut microbiota of 100 infants at newborn, 4 and 12 months. The results show that the multifractal dimensions of an infant's gut microbiomes can distinguish age differences.